Charcoal Rot and Yellow Mosaic Virus Diseases of Soybean Under Hot Spot Condition: Symptoms, Incidence and Resistance Characterization - Amrate, Pawan K.; Shrivastava, M. K.; Pancheshwar, Dinesh K.; Sharma, Stuti (International Journal of Bio-resource and Stress Management, 2020)
Charcoal rot (CR) and Yellow mosaic virus (YMV) caused by Macrophomina phaseolina (Tassi) Goid and Mungbean Yellow Mosaic India Virus (MYMIV), respectively are important soybean diseases in India. In a field experiment,forty one promising soybean genotypes across the country plus four check namely JS 20-29, JS 93-05, JS 95-60 and JS 335 were observed throughout the season (Kharif -2017) for different aspect of diseases including resistance evaluation. Incidence of YMV was higher in early stage and started declining after 60 days of crop. Whereas charcoal rot was very severe in later stage of crop and maximum plant mortality occurred in reproductive stages (60-75 days after sowing). Conspicuously, contrast yellow green patches (mottles) on the leaves in YMV and blackening on or below the epidermis of lower stem and root of infected dead plants in CR were major characteristic symptoms of respective disease, respectively. Out of forty one, only nine entries i.e. AUKS 174, JS 21-17, NRC 133, AMS 100-39, RVS 2011-1, RSC 11-07, PS 1611, RSC 11-03 and SKF-SPS-11 were found to be absolute resistant against CR. Whereas forty nine percent entries were exhibited susceptibility to highly susceptibility against CR with highest plant mortality of 86.5 per cent in JS 95-60. In case of YMV, thirty one entries were found to be highly resistant and highest coefficient of infection (22.60) was found in JS 93-05. Altogether, only six entries namely JS 21-17, AMS 100-39, RVS 2011-1, PS 1611, RSC 11-03 and SKF-SPS-11 were found to be absolutely/highly resistant against both the diseases (CR plus YMV).